1998
DOI: 10.1111/j.1439-0507.1998.tb00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytoses in Crete, Greece, between 1992 and 1996

Abstract: Pathological specimens from 1361 patients with clinical manifestations of dermatophytosis from the island of Crete, Greece, were examined for dermatophytes during a 5-year period (1992-96). Dermatophytes of the genus Trichophyton, Microsporum and Epidermophyton were isolated from 327 (24%) of the patients. Trichophyton rubrum was the most frequently isolated dermatophyte accounting for 44.4% of the strains, followed by M. canis (25%), T. mentagrophytes var. interdigitale (14.4%) and E. floccosum (7.6%). Less f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
2
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 21 publications
5
34
2
4
Order By: Relevance
“…It is responsible for most scalp infections, being the predominant agent detected at this region in most studies 12,13,14,15,18 . In the present study it was the second most frequent species, in agreement with the trend reported in a previous study conducted in São Paulo 46 and in European studies conducted in Spain, Greece and Italy 9,35,39 . In other regions, the frequency of M. canis varies, with the species being the third most frequent one in Rio Grande do Sul and Goiás (Brazil) and Argentina 12,13,15,31 , and being present at reduced percentages in Colombia and in the Amazon region 6,40,41 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is responsible for most scalp infections, being the predominant agent detected at this region in most studies 12,13,14,15,18 . In the present study it was the second most frequent species, in agreement with the trend reported in a previous study conducted in São Paulo 46 and in European studies conducted in Spain, Greece and Italy 9,35,39 . In other regions, the frequency of M. canis varies, with the species being the third most frequent one in Rio Grande do Sul and Goiás (Brazil) and Argentina 12,13,15,31 , and being present at reduced percentages in Colombia and in the Amazon region 6,40,41 .…”
Section: Discussionsupporting
confidence: 93%
“…Studies conducted in European countries, United States of America, Mexico and Argentina, also confirm the higher percentage of isolation of T. rubrum 10,15,23,34,35 . This is an anthropophilic fungus perfectly adapted to human keratinized tissues causing a mild chronic inflammation and rarely infects animals 49 .…”
Section: Discussionmentioning
confidence: 62%
“…Bu çalışmada renal transplantasyon yapılan hastalarda tespit edilen deri bulgularının normal populasyona göre artmış olduğu gözlenmiştir 4,5 . Özellikle immünsupresif tedavi kullanımına bağlı olarak bir çalışmada olduğu gibi infeksiyöz hastalıklar ön planda görülmektedir 6 .…”
Section: Discussionunclassified
“…Dosyaları taranan hastalarımızda mantar infeksiyonlarından onikomikoz tek başına ve/veya tinea pedis ile birlikte en sık gözlenen infeksiyon idi. Genel olarak baktığımızda normal populasyonda da mantar infeksiyonları en sık karşılaştığımız ve dermatoloji polikliniğine başvuruların önemli bir kısmını oluşturmaktadır 4 . Bu nedenle mantar infeksiyonlarının görülme sıklığının fazla olmasını transplantasyon hastalarındaki immünsupresyona duruma bağlamak doğru olmayacaktır.…”
Section: Discussionunclassified
“…Infection caused by fungi in man and animal are more common in tropical and subtropical countries due to prevailing moisture, over population, poor hygienic living conditions and temperature regimes [1][2][3][4][5]. Skin infection due to dermatophytes has become a severe health problem affecting children, adolescent and adults.…”
Section: Introductionmentioning
confidence: 99%